Application of Pedagogical Technologies on the Topic: "Polymer Composite Materials and their Significance": Penerapan Teknologi Pedagogis pada Topik: "Bahan Komposit Polimer dan Signifikansinya" - Khalovat Ismoilova (Academia Open, 2022)
Composite materials are soluble and insoluble, and its effectiveness is enhanced by the addition of additives. Natural and artificial composite materials, with a natural group of cellulose fibers in the body and stem of the plant, containing lignin, and for bones in the human and animal organism, the binding of thin, mature phosphate salts to plastic collagen is characteristic. Powder composite material (PCM) is characterized by resistance to deformation, cutting, welding, corrosion and heat .In the manufacture of disks and shovels, the properties of nickel-chromium alloys and powders with the addition of hafnium oxide are additionally improved.